Diagrammatic scale for evaluation of Bremia lactucae sporulation in lettuce seedlings - Jacinto, Ana Carolina Pires; Castoldi, Renata; Braz, Leila Trevisan [UNESP] (FapUNIFESP (SciELO), 2023)
In disease assessment, the use of diagrammatic scales provides a standard reference point for comparison. There is still no precise and accurate scale for the evaluation of sporulation intensity of downy mildew in lettuce seedlings. The objective of this study was to propose a diagrammatic scale for the evaluation of downy mildew severity in lettuce seedlings. Thirty lettuce seedlings with different sporulation intensities were used to develop the proposed diagrammatic scale. Solaris lettuce cultivar was sown, and fifteen days after sowing, inoculations occurred using distilled water, the pathogen sporangia, and Tween 20. The monitoring of disease development was performed daily.When the first sporulation appeared on the cotyledonaryleaves,the proposed scale was verified to meet the minimum and maximum levels of disease severity. Two evaluators verified the accuracy, precision and performed the estimation of the sporulation and reproducibility using a scale. The images obtained are important in the standardization of a scale to identify resistant, tolerant and susceptible plants to downy mildew. Furthermore, it allows validating a diagrammatic scale of sporulation intensity of B. lactucae in lettuce seedlings. Thus, it is the diagrammatic scale developed in the work will guide future research to accelerate the detection of mildew severity in lettuce seedlings
Keywords: disease severity; downy mildew; Lactuca sativa; rating scale